The Effect of Current Ratio and Receivable Turnover On Profitability (Study of PT X Financial Reports for the 2016-2021 period) - Hanifah, Azimah (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The aim of this research is to determine and analyze: (1) Current Ratio (2) Receivable Turnover; (3) Profitability; and (4) The influence of Current Ratio and Receivable Turnover on Profitability at PT. X Period 2016-2021, both simultaneously and partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this research is the financial report of PT. X Period 2016-2021. The type of investigation is causality, and the time horizon in this research is time-series. Based on the research results, it was found that the Current Ratio at PT. X Period 2016-2021, apparently gave good analysis results, Receivable Turnover at PT. X The 2016-2021 period can generally be said to be good, Profitability at PT. X The 2016-2021 period is currently considered good. Current Ratio and Receivable Turnover on Profitability at PT. X Period 2016-2021 has a significant effect simultaneously or partially. However, partially Receivable Turnover predominantly influences Profitability rather than Current Ratio. Because Receivable Turnover predominantly influences Profitability, it is the first priority in increasing Profitability. then PT. X is advised to consistently improve receivables turnover, so that the company's financial performance improves.